The assessment of the control of vestibular system 2018 - มหาสิทธิวัฒน์, วิศาล (Journal of Medicine and Health Sciences, 2018)
One of the common complaints that bring patients consult doctor is vertigo. Therefore, its caused by vestibular dysfunctions. The assessment composes with specific history, neurological examination, oculomotor testing, nystagmus including vestibular function test. Accordingly, this up-to-date article will support physician to evaluate the vestibular system to confirm the diagnosis, localizing lesions, a degree of severity and ensuring stage of improvement with evidence-based medicine.